A study on the hydrogen storage properties and reaction mechanism of Na3AlH6LiBH4 composite system. (26th April 2018) - Halim Yap, F.A.; Mustafa, N.S.; Yahya, M.S.; Mohamad, A.A.; Ismail, M.
Abstract: In this work, the hydrogen storage properties of different molar ratio (in mole of 1:3 and 1:4) Na3 AlH6 LiBH4 system is investigated for the first time. X-ray diffraction and Fourier transform infrared results show that the Na3 AlH6 LiBH4 with molar ratio of 1:3 and 1:4 composite was transformed to Li3 AlH6 and NaBH4 phases via a metathesis reaction during a ball-milling process for 6 h. Temperature-programmed-desorption (TPD) results show three stages of decomposition for the Na3 AlH6 LiBH4 (in mole ratio of 1:3 and 1:4) composite resulting from Li3 AlH6 and NaBH4 phases. From the TPD graph, the Na3 AlH6 LiBH4 composite with molar ratio of 1:4 had showed better performance of hydrogenation properties compared to with molar ratio of 1:3. The composite began to release hydrogen at 180 °C in relation to decomposition of the Li3 AlH6 stage into LiH and Al. The NaBH4 stage then began to decompose at approximately 380 °C, after reacting with Al to form an intermetallic phase, AlB2, which occurred at 100 °C lower than as-milled NaBH4 . At 430 °C, the un-reacted NaBH4 was decomposed after catalysing with AlB2 . Kissinger analysis shows the apparent activation energy of NaBH4 decomposition in the hydrides composite was reduced by about 75 kJ/mol compared to the as-milled NaBH4 . The rehydrogenation process evidenced the reversibility of NaBH4 . Based on these results, the intermetallic phase, AlB2, is considered to have played an important role by lowering the operating temperature and providing access to the full hydrogen content in the Na3 AlH6 LiBH4 composite system. Highlights: H2 storage properties of Na3 AlH6 LiBH4 were investigated for the first time. Na3 AlH6 LiBH4 was transformed to Li3 AlH6 /NaBH4 phases via a metathesis reaction. The intermetallic phase, AlB2 is considered to have played an important role.